How digitalisation is changing your business. [Themenschwerpunkt]. - (:unkn) unknown (Union Internationale des Transport Publics, 2017)
Die Themen im Einzelnen: K. McHugh: Magic Numbers: How Big Data is helping to improve public transport assets (S. 20-23). L. Brown: Digitalisation and customer experience. Towards satisfaction guaranteed? (S. 24-27). Developing talent in the digital era (S. 28-30). R. Walch / L. Brown: Stakes are high in cyber security for transport (S. 32-34). K. McHugh: Greater than the sum of its parts (S. 35-38).
Keywords: Öffentlicher Verkehr; Verkehrsunternehmen; Technikstand; Kommunikationstechnologie; Informationstechnologie; Verkehrsplanung; Planungsmethode; Verkehrsbauwerk; Entscheidungsfindung; Berufsqualifikation; Zukunft; Big Data; Vernetzung; Digitalisierung; Kundenfreundlichkeit; Fahrgastinformation; Datensicherheit; Informationssicherheit; Datenauswertung; Building Information Modeling (BIM)